STRATEGI KOMUNIKASI DIGITAL FRAKSI PARTAI DEMOKRAT DALAM OPTIMALISASI PENYEBARAN INFORMASI PUBLIK: Peran Fraksi Partai Demokrat dalam Diseminasi Informasi Publik - Adinda, Hanania; Santoso , Hudi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The role of public relations in government institutions is crucial as a facilitator of communication between the agency and the public, both internal and external. In the digital era and the context of public information openness, public relations are required to convey information transparently, accountably, and in a manner that is easily accessible to the public. This study highlights the importance of digital communication strategies in supporting public information openness through the utilization of social media, particularly Instagram and official websites, as demonstrated by the Democratic Party Faction (@fpd_dpr). These platforms were chosen due to their high usage rates in Indonesia and their ability to disseminate information quickly and broadly. However, the effectiveness of this communication still faces several challenges, including limitations in access and digital literacy among the public, a lack of meaningful two-way interaction, difficulties in maintaining transparency, and information overload without appropriate delivery strategies. A comprehensive digital communication strategy plan and implementation are needed for public relations to perform its functions optimally, build public trust, and support government transparency.